PENERAPAN MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA POKOK BAHASAN BANGUN DATAR SISWA KELAS IV SDN 171/IV KOTA JAMBI - Hendriani; Indriyani; Ugi Nugraha; Urip Sulistiyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Picture and Picture learning model is a learning model where the teacher uses tools or image media to explain material or facilitate students to actively learn. By using tools or image media, it is hoped that students will be able to follow lessons with good focus and in pleasant conditions. So that whatever message is conveyed is usually well received and able to sink into the heart, and can be remembered again. This Classroom Action Research (PTK) was carried out in two cycles with the main material: Bangun Datar. The data collection tools used consist of learning instruments, evaluations (tests) and observations to determine data validation. The subjects studied were teachers and class IV students at SDN 171/IV Jambi City. The results of the research show that by using the Picture and Picture learning model, student learning outcomes in each cycle have increased significantly. These changes, which were previously bad, have become better. Consecutively (based on cycle I and cycle II) the Mathematics learning results of class IV students at SDN 171/IV Jambi City on the main subject Flat building in cycle I obtained an average score of 76.84. Of the 19 students, as many as 6 students (32%) did not complete because the scores obtained did not reach the expected KKM, namely 70. So the percentage of student completion obtained was 70%. Meanwhile, the classical Completeness Standard is classically considered to have completed learning if 80% of the number of students achieve a minimum absorption capacity of 70. Meanwhile, in cycle II the data obtained an average value of 84.11. Of the 19 students, as many as 2 students (11%) did not complete because the scores obtained did not reach the expected KKM, namely 70. So the percentage of student completion obtained was 90%. Meanwhile, the classical Completeness Standard is classically considered to have completed learning if 80% of the number of students achieve a minimum absorption capacity of 70. The application of the Picture and Picture learning model can ultimately improve the Mathematics learning outcomes of class IV students at SDN 171/IV Jambi City.